The new politics and geographies of scarcity. Issue 101 (May 2019) - Mehta, Lyla; Huff, Amber; Allouche, Jeremy
Abstract: Scarcity is a dangerous idea and has long been a totalising discourse in resource politics and mainstream economics. A large body of work has critiqued the naturalisation of scarcity in discourses of environmental change, and has highlighted problems in how scarcity is conceptualised and the ways in which scarcities are socially and politically generated. Despite this, the 'scarcity postulate' – an assumed mismatch between infinitely expanding human desires and finite means to realise them – remains a powerful concept that continues to be deployed and re-deployed in a host of debates concerning environment and natural resources. From the 'Limits to Growth' debates that influenced environmental movements in the 1970s, discussions concerning the causes and consequences of the overlapping food, fuel and finance crises of the 2000s to debates concerning climate change, environmental security and militarisation in the Anthropocene, the discursive constellation of scarcity seems always at work. The focus of this special issue is the cross-scalar dynamics of what we identify as a 'new politics of scarcity'. This new politics is associated with new framings, contestations and entanglements of scarcity that are associated with new configurations of actors, new political economic relations and new spatialities and geographies of resource control and violence. Building on the empirical cases developed in this special issue, we examine the dynamics and the 'work' of the new cross-scalar scarcity politics in sustaining elite and capitalist power through justifying resource acquisitions and enclosures, large-scale policy reforms in the name of 'austerity' and intensification of extraction whilst politically side-stepping more thorny politics of (re)distribution, mis-appropriation, dispossession and social justice. We conclude by looking at alternative framings and vernacular conceptions of sustainability that challenge dominant scarcity-driven policies and programmes that intensify local exclusions and inequalities.